Combination of Venetoclax and Midostaurin Efficiently Suppressed Relapsed t(8;21)Acute Myeloid Leukemia With Mutant KIT After Failure of Venetoclax Plus Azacitidine Treatment - Li, Zheng; Wang, Jun; Ge, Shuai-Shuai; Qiu, Qiao-Cheng; Du, Jia-Hui; Shan, Shuang-Shuang; Shen, Xiang-Dong; Wan, Chao-Ling; Wang, Bin-Ru; Wu, De-Pei; Qiu, Hui-Ying; Xue, Sheng-Li (Frontiers in Oncology, 2022)
Acute myeloid leukemia (AML) with t(8;21) is categorized as favourable-risk AML, but KIT mutations show a significantly poor prognostic impact in such patients. Persistent vulnerability to relapse is a major challenge in the treatment of this subtype of patients. Venetoclax is a BCL-2 selective inhibitor. The venetoclax+HMA strategy is also a notable salvage regimen that achieves good clinical outcomes in the treatment of relapsed or refractory (R/R) AML. However, in our clinical practice, we found that disease progressed rapidly even after venetoclax+azacitidine (AZA) therapy in two relapsed t(8;21) AML patients with KIT mutations. We report for the first time the therapeutic potential of venetoclax+midostaurin as a new combination therapy for relapsed t(8;21) AMLs with KIT mutations showing resistance to venetoclax+AZA therapy. Our ex vivo study also showed that midostaurin alone could inhibit proliferation and induce apoptosis of Kasumi-1 cells (e.g. Midostaurin induced G2 phase cell arrest, down-regulated p-KIT and BCL-2, while Bax protein levels were up-regulated) and observed a synergistic anti effect when the two drugs were combined. Our study shows that the venetoclax+midostaurin regimen may be a promising treatment option for R/R t(8;21) AML with KIT mutations.